Altitude training and endurance performance - Robach, P.; Lundby, C. (Triathlon Medicine, 2019)
Many endurance athletes use altitude training to improve their physical performance. In this chapter, we briefly present the main altitude training methods and we evaluate from the existing scientific data their potential effectiveness on endurance performance at sea level. Live high-train high (LHTH) at natural altitude has not been demonstrated to improve endurance performance, which contrasts with the method's popularity, including among elite triathletes. Live high-train low (LHTL) at natural or simulated altitude has been quite extensively studied. However, this approach remains a controversial topic and robust evidence that LHTL increases endurance performance in athletes is lacking. Finally, evidence indicate that live low-train high (LLTH), generally implemented at simulated altitude, has no positive effect on endurance performance and may therefore not be recommended for triathletes. While recognizing the scientific controversies that exist regarding the effectiveness of altitude training on endurance performance, this review also provides practical recommendations to triathletes wishing to prepare at altitude.